Mentor Texts: Models to Improve False Beginners’ Writing Skills - Hesthi Herusatoto (Universitas Cokroaminoto Palopo, 2018)
This research was to find out the effects of mentor texts on students’ ability to write a descriptive paragraph. Changes in the content and organization of their paragraphs were examined closely. As many as 35 students majoring in nursing who were enrolled in an English class participated in this research. In the class, the students learned to write a descriptive paragraph using some mentor texts which served to help them learn identifying and writing a topic sentence, supporting sentences, and a concluding sentence. The texts also provided them with models to make a paragraph have unity and coherence. The data were collected from the student’ paragraphs produced before and after the learning process and the paragraph they wrote in the delayed posttest. A survey was also distributed at the end of their English class to collect their responses on the use of mentor texts in their learning process. The findings of this research indicated that mentor texts indeed had positive effects on the students’ ability to write a descriptive paragraph. Their awareness to include a topic sentence, details, unity, a concluding sentence, and transition signals in their paragraph was found to significantly develop. In addition, mentor texts enhanced the students’ confidence, interest, and motivation in writing.